Predictive value of TP53 RNAscope® in situ hybridization and p53 immunohistochemistry for TP53 mutational status in canine diffuse large B-cell lymphoma - Greta Foiani; Luca Licenziato; Laura Marconato; Antonella Fanelli; Erica Melchiotti; Claudia Zanardello; Luca Aresu; Marta Vascellari (Veterinary Quarterly)
TP53 mutations are associated with short survival and poor treatment response in canine diffuse large B-cell lymphoma (cDLBCL). The expression of TP53 by RNAscope® in situ hybridization and p53 by immunohistochemistry (IHC) was investigated in 37 formalin-fixed paraffin-embedded cDLBCL, to assess their correlation with TP53 mutational status and to evaluate their prognostic value. TP53 was detected in all samples by RNAscope®. Ten of 37 (27%) cases expressed p53 by IHC, with highly variable percentage of positive cells. TP53 RNAscope® scores and p53 IHC results were not correlated. The expression of TP53 by RNAscope® was not influenced by its mutational status. Conversely, p53 IHC and TP53 mutations were significantly associated. p53 IHC predicted TP53 genetic mutations with high accuracy (97.3%). All TP53-mutated samples carrying missense mutations exhibited p53 expression by IHC, while all wild-type cases and a single case with frameshift insertion were negative. In univariable analysis, p53 IHC was associated with shorter time to progression (TTP) and lymphoma-specific survival (LSS). Nevertheless, in multivariable analysis, only treatment significantly affected TTP and LSS. These findings suggest p53 IHC is an accurate, cost-effective tool for predicting TP53 mutations in cDLBCL, unlike TP53 RNAscope®, though its prognostic value requires further validation.